Correlation Between AI Usage and Students' Perceptions in Learning Kirchhoff's Law at Senior High School in South Jakarta - Rahma Amelia Oktapiani; Dwi Nanto (Universitas Negeri Semarang, 2026)
The Artificial Intelligence (AI) in Physics learning is growing. However, the correlation between AI usage and supporting students' understanding of basic electrical concepts, such as Kirchhoff's Law, still requires further investigation. The correlation between the level of AI usage and students’ perceptions of its benefits in learning Kirchhoff’s Law at several senior high schools was investigated in this study. Using an exploratory sequential mixed methods design, this study involved 250 students as quantitative respondents. They were divided into two groups based on their physics exam scores. One respondent represents the group that has a minimum of 80 points. Certainly, one respondent represents above or equal to more than 80 points. The questionnaire instrument was verified by two experts in the subject matter and educational technology. Quantitative results indicate that students' assessment of AI usage falls into the excellent category with an average indicator score of four. The groups with scores less than or equal to 80 tend to use AI more frequently and experience its benefits directly. Meanwhile, the groups with scores greater than 80 appear to have more experience in AI usage. Spearman's correlation analysis indicated a significant relationship between the frequency of AI usage and its preferences for the students. Qualitative results show that AI usage accelerates students' conceptual understanding of physics material, but they still have limitations in explaining complex Physics formulas. Overall, this research concludes that AI usage shows good potential in assisting the learning process of Kirchhoff's Law.